A multi-centre analysis of a decade of endoscopic pharyngeal pouch surgery in Cheshire and Merseyside. Issue 10 (3rd October 2020) - Hampton, T; Allan, J; Pearson, D; Emerson, H; Jones, G H; Junaid, M; Kanzara, T; Lau, A S; Siau, R; Williams, S P; Wilkie, M D
Abstract: Background: There are sparse data on the outcomes of endoscopic stapling of pharyngeal pouches. The Mersey ENT Trainee Collaborative compared regional practice against published benchmarks. Methods: A 10-year retrospective analysis of endoscopic pharyngeal pouch surgery was conducted and practice was assessed against eight standards. Comparisons were made between results from the tertiary centre and other sites. Results: A total of 225 procedures were performed (range of 1.2–9.2 cases per centre per year). All centres achieved 90 per cent resumption of oral intake within 2 days. All centres achieved less than 2-day hospital stays. Primary success (84 per cent (i.e. abandonment of endoscopic stapling in 16 per cent)), symptom resolution (83 per cent) and recurrence rates (13 per cent) failed to meet the standard across the non-tertiary centres. Conclusion: Endoscopic pharyngeal pouch stapling is a procedure with a low mortality and brief in-patient stay. There was significant variance in outcomes across the region. This raises the question of whether this service should become centralised and the preserve of either tertiary centres or sub-specialist practitioners.